Treating Inflammation Associated with Pulmonary Hypertension: An Overview of the Literature - Yoo, Hugo Hyung Bok [UNESP]; Marin, Flávia Luiza (Taylor & Francis, 2022)
Pulmonary hypertension (PH) comprises five groups of serious clinical entities characterized by pulmonary artery vasoconstriction and vascular remodeling leading to right heart failure and death. In addition to vascular remodeling, recruitment and exaggerated accumulation of several perivascular inflammatory cells is also observed, including macrophages, monocytes, T and B-lymphocytes, dendritic cells and mast cells distributed in pulmonary perivascular spaces and around remodeling pulmonary vessels. Current pulmonary arterial hypertension (PAH)-targeted therapies aim to improve functional capacity, pulmonary hemodynamic conditions, and delay disease progression. Nevertheless, PAH remains incurable, with a poor prognosis and is often refractory to drug therapy, highlighting the need for further research. In the last three decades, the best pathophysiological understanding of PAH has allowed for progression from a disease of little-known pathogenesis, without specific and effective therapy to expanding the arsenal of drugs on a cellular, genetic and molecular basis. This article provides an overview on current knowledge and progress in recent advances in pharmacological therapy in PAH.
Keywords: Inflammation; Pulmonary arterial hypertension; Treatment